Konsep Tuhan pada Agama Kristen dalam Prespektif Islam - Juhansar Andi Latief (Al-Ulum, 2011)
This article provides a concept of God in the Christianity. The concept is based on the Islamic perspective. It briefly explains how the Christian concept of God explores descriptive and then compare and contrast these insights, the concept of God which is based on the two Abrahamic faiths, Christianity and Islam. It also looks at some of the criticism of Islam on the concept of God in Christianity. The study then found that even those two religions have the same root as the Abrahamic religions but they actually have different interpretations of the concept of God itself. Unlike the tradition of Islam, Christianity has the concept of the trinity of God.